Lumen Christi: The Stained Glass Windows of Mount Saint Joseph Abbey - Funk, Mary Margaret (Cistercian studies quarterly, 2011)
The article reviews the book "Lumen Christi: The Stained Glass Windows of Mount Saint Joseph Abbey," by Laurence Walsh.